Sistem Informasi Persediaan Barang Habis Pakai Pada Dinas Lingkungan Hidup - Kurniawansyah, Deni; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2023)
The rapidly expanding of information technology nowadays as well as the implementation ofcomputerized systems has almost been used in all fields, including at Environment ServiceJambi City.These days, Environment Services in Jambi city still using manual methods in the way of consumableitems management. The aim of this study is to analyze, design, consumables inventory informationsystem, receipt of consumables, demand for consumables, distribution of consumables, and recordingreports used UML Unified Modeling Language) that are consist of Use Case Diagram, Activity DiagramDan Class Diagram and design to the extent of prototype. This research produces a prototype informationsystem of consumable items supplies that can be manage by computerized system that can present reportsof consumables needed daily or every month thatcan be applied to support the entire inventoryinformation system of consumablesitem in at Environment services in Jambi city.